Omission bias and vaccine rejection by parents of healthy children: implications for the influenza A/H1N1 vaccination programme. - Brown, K; Kroll, J; Hudson, M; Ramsay, M; Green, J; Vincent, C; Fraser, G; Sevdalis, N (2010)
2009 H1N1 influenza A ("swine flu") vaccine has been offered to healthy UK children aged 6 months-5 years since December 2009, though around 50% of parents plan to reject the vaccine. This study examined whether such parents exhibit omission bias (preference for errors arising from inaction over errors arising from action). One-hundred and forty-two parents completed an online questionnaire in which they rated (a) probability of occurrence, (b) symptoms and (c) duration of a hypothetical disease and a hypothetical vaccine adverse event (VAE). Almost all attributes were rated significantly less favourably when relating to VAE than to disease (p<0.01 for 17 of 22 outcomes), despite the attributes being objectively identical. These data suggest that any vaccine is at a disadvantage in many parents' consciousness in comparison with the infection itself, and that minor safety concerns could have disproportionately detrimental effects on vaccine uptake. Behavioural science offers strategies to ameliorate the impact of this bias and these should be explored further.